FORECASTING VOLCANIC ERUPTIONS - Sparks R.S.J. (My University, 2003)
Forecasting is a central goal of volcanology. Intensive monitoring of recent eruptions has generated integrated time-series of data, which have resulted in several successful examples of warnings being issued on impending eruptions. Ability to forecast is being advanced by new technology, such as broad-band seismology, satellite observations of ground deformation and improved field spectrometers for volcanic gas studies, and spectacular advances in computer power and speed, leading to improvements in data transmission, data analysis and modelling techniques. Analytical studies of volcanic samples, experimental investigations and theoretical modelling are providing insights into the dynamics of magmatic systems, giving a physical framework with which to interpret volcanic phenomena. Magmas undergo profound changes in physical properties as pressure and temperature vary during magma chamber evolution, magma ascent and eruption. Degassing and cooling during magma ascent induce crystallisation and increases of viscosity, strength and compressibility, commonly by several orders of magnitude. Active magmatic systems also interact strongly with their surroundings, causing ground deformation, material failure and other effects such as disturbed groundwater systems and degassing. These processes and interactions lead to geophysical and phenomenological effects, which precede and accompany eruptions. Forecasting of hazardous volcanic phenomena is becoming more quantitative and based on understanding of the physics of the causative processes. Forecasting is evolving from empirical pattern recognition to forecasting based on models of the underlying dynamics. The coupling of highly non-linear and complex kinetic and dynamic processes leads to a rich range of behaviours. Due to intrinsic uncertainties and the complexity of non-linear systems, precise prediction is usually not achievable. Forecasts of eruptions and hazards need to be expressed in probabilistic terms that take account of uncertainties.